A structural and functional analogue of a Bowman–Birk-type protease inhibitor from Odorrana schmackeri. Issue 2 (28th April 2017) - Wu, Yuxin; Long, Qilin; Xu, Ying; Guo, Shaodong; Chen, Tianbao; Wang, Lei; Zhou, Mei; Zhang, Yingqi; Shaw, Chris; Walker, Brian
Abstract : Frog skin secretions contain complex peptidomes and peptidic protease inhibitors that are one of the biologically and structurally described groups of components. In the present study, by use of molecular 'shotgun' cloning and LC MS/MS fractionation sequencing, a novel Bowman–Birk-type heptadecapeptide (AALKGCWTKSIPPKPCF-amide), named O dorranas chmackeri T rypsinI nhibitor (OSTI), with a canonical Cys 6 –Cys 16 disulfide bridge, was isolated and identified in piebald odorous frog ( O. schmackeri ) skin secretion. A synthetic replicate of OSTI-exhibited trypsin inhibitory activity with a K i value of 0.3 ± 0.04 nM and also a tryptase inhibitory effect with a K i of 2.5 ± 0.6 μM. This is the first time that this property has been reported for a peptide originating from amphibian sources. In addition, substituting lysine (K) with phenylalanine (F) at the presumed P1 position, completely abrogated the trypsin and tryptase inhibition, but produced a strong chymotrypsin inhibition with a K i of 1.0 ± 0.1 μM. Thus, the specificity of this peptidic protease inhibitor could be optimized through modifying the amino acid residue at the presumed P1 position and this novel native OSTI, along with its analogue, [Phe 9 ]-OSTI, have expanded the potential drug discovery and development pipeline directed towards alleviation of serine protease-mediated pathologies.